French Islamophobia: How Orthopraxy Is Conceptualized as a Public Peril - Christina Lienen; Samir Sweida-Metwally (Religions)
For over two decades, France’s Muslim population has faced a series of legal measures and hostile public narratives aimed at problematizing their faith. Notable examples include the 2004 national ban on “ostentatious religious symbols” in state schools, which prohibits obligatory religious dress in various settings. These individual instances are compounded by more recent broader policies, decisions, laws, and executive statements that negatively impact Muslim life. This paper examines France’s trajectory from a new perspective: A Muslim legal viewpoint. It argues that the French approach constitutes a two-step process of institutionalized Islamophobia, understood here as hostility towards Islam as a faith. First, the state redefines mainstream Islamic orthopraxy as “extreme”, pitting ordinary religious practices against averred Republican values. Second, it seeks to promote an alternative concept of a “French Islam”—one that aligns with France’s secular principles and is stripped of its religious essence—positioning it as the only acceptable framework for Muslims to practice their faith in France. We argue that this process is not about upholding laïcité or state neutrality; rather, invoking the latter serves as a smokescreen for the state’s Islamophobia.